2019
DOI: 10.3390/rs11080895
|View full text |Cite
|
Sign up to set email alerts
|

Wet and Dry Snow Detection Using Sentinel-1 SAR Data for Mountainous Areas with a Machine Learning Technique

Abstract: Traditional studies on mapping wet snow cover extent (SCE) often feature limitations, especially in vegetated and mountainous areas. The aim of this study is to propose a new total and wet SCE mapping strategy based on freely accessible spaceborne synthetic aperture radar (SAR) data. The approach is transferable on a global scale as well as for different land cover types (including densely vegetated forest and agricultural regions), and is based on the use of backscattering coefficient, interferometric SAR coh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
81
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 62 publications
(82 citation statements)
references
References 86 publications
1
81
0
Order By: Relevance
“…In addition to the temperature information, vegetation indexes might also help to detect SCE especially in forested regions. In a previous study, we found [18] that the densely vegetated regions tend to show lower SCE mapping accuracy when compared to, e.g., bare area, sparse vegetation, and grassland. Moreover, previous studies also suggested that SAR backscatter, InSAR coherence, and PolSAR parameters are all related to vegetation types and conditions [23,[32][33][34].…”
Section: Introductionmentioning
confidence: 82%
See 4 more Smart Citations
“…In addition to the temperature information, vegetation indexes might also help to detect SCE especially in forested regions. In a previous study, we found [18] that the densely vegetated regions tend to show lower SCE mapping accuracy when compared to, e.g., bare area, sparse vegetation, and grassland. Moreover, previous studies also suggested that SAR backscatter, InSAR coherence, and PolSAR parameters are all related to vegetation types and conditions [23,[32][33][34].…”
Section: Introductionmentioning
confidence: 82%
“…For PolSAR parameters, the polarimetric matrix was first constructed from the calibrated and debursted SLC images and the derived eigenvalues and eigenvectors were then used for calculating H/A/α parameters [20]. For a more detailed description of the SAR pre-processing, we refer to Tsai et al (2019) [18].…”
Section: Methodsologymentioning
confidence: 99%
See 3 more Smart Citations